2022
DOI: 10.1038/s41598-022-11336-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient quality and maturity status of frass fertilizer from nine edible insects

Abstract: Globally, there is growing interest to recycle organic waste using insect larvae into high-quality frass fertilizer through circular economy approach. This paper presents the first comparative report on the nutrient concentrations, fertilizing indices, nutrient supply potentials and compost maturity of nine edible insect frass fertilizers. Our results revealed that frass fertilizers from all the insect species had adequate concentrations and contents of macronutrients [nitrogen (N), phosphorus (P), potassium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 70 publications
1
28
1
1
Order By: Relevance
“…This may explain early seedling inhibition but the absence of long-term effect during plant growth. Contrary to Beesigamukama who suggested that prior composting of T. molitor frass was necessary to circumvent phytotoxic effects, our results suggest that soil processes after application are sufficient to promote plant growth and yield with T.…”
Section: Results and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This may explain early seedling inhibition but the absence of long-term effect during plant growth. Contrary to Beesigamukama who suggested that prior composting of T. molitor frass was necessary to circumvent phytotoxic effects, our results suggest that soil processes after application are sufficient to promote plant growth and yield with T.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…These authors suggest that T. molitor frass high salt concentration and electrical conductivity could explain seedling phytotoxicity. 53 Kebrom et al 54 discussed the strong phytotoxic effects of hen manure on the germination of collard greens. Hence, our results confirm that germination decrease is not different between insects and hen manure.…”
Section: Resultsmentioning
confidence: 99%
“…Edible insects provide considerable environmental benefits, for example, by assisting in pollination activities, bio-degradation activities and humus formation, while also assisting in improving soil structure [ 27 ]. In addition, edible insects are also emerging as key in the recycling of organic waste into frass fertilisers that are of high quality in nature [ 61 ]. Some insects that have proven their capability in producing frass fertilisers include the black soldier fly, P.sinuata , O.rhinoceros and H.illucens [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, edible insects are also emerging as key in the recycling of organic waste into frass fertilisers that are of high quality in nature [ 61 ]. Some insects that have proven their capability in producing frass fertilisers include the black soldier fly, P.sinuata , O.rhinoceros and H.illucens [ 61 ]. The utilisation of insects in the recycling of organic waste promotes cleaner sustainable production systems and decreases environmental contamination [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the farmed species and the substrate used to grow the insects, the general composition of frass can be highly diverse. However, its fertilizing effect is associated with the high content of organic carbon, nitrogen, and phosphorus that are comparable to other organic fertilizers (Beesigamukama et al, 2022). In addition, the chitin contained in shed skins or dead insects has been shown to improve plant immune responses and stress tolerance by simulating contact with potential pest insects (Barragán-Fonseca et al, 2022).…”
Section: Introductionmentioning
confidence: 99%